Sulfide Removal by Catalitic Oxidation From Rayon Waste - Wulansari, Isma (Green Publisher Indonesia, 2023)
Catalytic oxidation of spent sulfidic caustic consist of SH- ion or NaHS compound by H 2 O2 in neutral or acidic solution to elemental sulphur may provide a convenient and economical method for the control of sulphide wastes and their associated odors at pulp, paper and textile industry. Oxidation of sulfide in rayon waste by hydrogen peroxide was investigated in the presence of ferric sulfate catalyst. Kinetic equations and activation energies of H 2 O2 and SH- ion to total sulphur and sulphate in rayon waste for catalytic oxidation reaction were calculated based on the experimental results. For the removal of sulfide from sulfide solution the most common process involves its catalytic oxidation to a more benign form sulfate. The rate of sulfidic catalytic oxidation was found higher at lower initial sulphide concentration and the rate of sulphide catalytic oxidation was found directly proportional to loading and hydrogen peroxide addition. Optimum total sulphide concentration was achieved when sulphide solutions in the presence of H 2 O 2 in the ratios SH-/H 2 O 2 1:4.2. The potential user of H 2 O 2 determine the optimal conditions for control of odor, corrosion and waste treatment cost due to sulfide consisting of sulphur ion, sulphate ion, etc. The catalytic oxidation of sulphides into sulphates by H 2 O 2 may be applied directly to aqueous wastes containing these odorants